Thermal distribution and reliability prediction for 3D Networks-on-Chip - Dang, Khanh N.; Ben Ahmed, Akram; Ben Abdallah, Abderazek; Tran, Xuan-Tu (VNU Journal of Science: Computer Science and Communication Engineering; Vol 36 No 1 (2020)DO - 10.25073/2588-1086/vnucsce.245, 2020)
As one of the most promising technologies to reduce footprint, power consumption and wire latency, Three Dimensional Integrated Circuits (3D-ICs) is considered as the near future for VLSI system. Combining with the Network-on-Chip infrastructure to obtain 3D Networks-on-Chip (3D-NoCs), the new on-chip communication paradigm brings several advantages. However, thermal dissipation is one of the most critical challenges for 3D-ICs, where the heat cannot easily transfer through several layers of silicon. Consequently, the high-temperature area also confronts the reliability threat as the Mean Time to Failure (MTTF) decreases exponentially with the operating temperature as in Blackâ€™s model. Apparently, 3D-NoCs and 3D ICs must tackle this fundamental problem in order to be widely used. However, the thermal analyses usually require complicated simulation and might cost an enormous execution time. As a closed-loop design flow, designers may take several times to optimize their designs which significantly increase the thermal analyzing time. Furthermore, reliability prediction also requires both completed design and thermal prediction, and designer can use the result as a feedback for their optimization. As we can observe two big gaps in the design flow, it is difficult to obtain both of them which put 3D-NoCs under thermal throttling and reliability threats. Therefore, in this work, we investigate the thermal distribution and reliability prediction of 3D-NoCs. We first present a new method to help simulate the temperature (both steady and transient) using traffic values from realistic and synthetic benchmarks and the power consumption from standard VLSI design flow. Then, based on the proposed method, we further predict the relative reliability between different parts of the network. Experimental results show that the method has an extremely fast execution time in comparison to the acceleration lifetime test. Furthermore, we compare the thermal behavior and reliability between Monolithic design and TSV-based design.  We also explore the ability to implement the thermal via a mechanism to help reduce the operating temperature.